A sound education: Becoming aware of the sound around us - De Oliveira Fonterrada, Marisa Trench [UNESP] (My University, 2011)
In this article it is intended to discuss the issue of noise pollution from an unusual point of view: noise pollution is not only the result of sound increase worldwide, but, particularly, the poor quality of our listening habits in modern life as well. In contemporary society we are subject to a considerable amount of stimulus to all our senses: vision, scent, taste and hearing which are becoming more and more insensible due to over exposure in our environment. These increased stimuli make us look for alternatives to reduce our ability to perceive them and be protected from injuries. However, our sensitivity will also decrease. In the specific case of environment noise, over exposure has made us forget the enchantment of certain sounds that used to give us pleasure or evoke good feelings by many ways, making us recall certain good things, bringing particular moments of our lives to our memory or even filling us with strong emotion. The Canadian composer and music educator, R. Murray Schafer, believes that noise pollution is the result of a society who became deaf. Closing our ears to noise protect us from noise pollution but also prevent us from grasping subtleties of listening. Contemporary world does not help us to be aware of sound in the space around us; acquiring this hearing ability is a matter of focus, interest and practice. Sound education exercises are aimed at children, teenagers and adults who want to improve their listening ability to environmental sounds, perceive its proprieties and learn how sound affects us and touches our feelings. The results are easy to accomplish and contribute to our awareness of the sound environment around us and to the conception of the environmental sound as a composition made by everybody and everything through positive actions, strong will and high sensitivity. Copyright © (2011) by the International Institute of Acoustics & Vibration.
Keywords: Environmental sounds; High sensitivity; Sound environment; Audition; Education; Noise pollution; Acoustic noise